Characterization of Fish Skin Gelatin Yellowfin Tuna - Mala Nurilmala; Agoes Mardiono Jacoeb; Rofi Ahmad Dzaky (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Gelatin is one of the products which become a necessity for various industries, i.e. food and non-food industries. The application of gelatin has been increasing year by year in Indonesia. However, there is nogelatin industry in Indonesia so far. Thus, it is necessary to find an alternative source of gelatin, especially from fishery by products.Thus, the purpose of this research was to extract fish skin gelatin of yellowfin tuna with temperature treatments (55, 65 and 75oC). In addition, the properties of resulted gelatin were determined including yield, pH, gel strength, viscosity, functional groups, molecular weight profiles, and amino acid composition. The extraction at 75oC was chosen as the best result. The yield was 17%; pH 5.3; gel strength 1789.55 gf, viscosity 104.2 Cp, respectively. There was functional group amide A, I, II, dan III. SDS-PAGE showed β, α1 dan α2 bands for tuna skin gelatin. In addition, the main amino acids were glycine and proline.